Performance of Wheat Varieties Under Late Planting-Induced Heat Stress Condition - Rahman, MM; Hasan, MA; Chowdhury, MF; Islam, MR; Rana, MS (Bangladesh Agronomy Journal, 2018)
The effect of late planting heat stress on physiological traits, yield attributes and yield of four wheat varieties (BARI Gom 25, BARI Gom 26, BARI Gom 28 and Sourav) were tested in the study. November 30 sowing was considered as control and December 30 sowing as the late planting heat stress condition. Wheat Var. BARI Gom 25, BARI Gom 26 and BARI Gom 28 showed greater stability of flag leaf chl, higher level of proline in flag leaf and kernel and greater ability to keep the canopy cooler compared to Sourav under late planting heat stress condition. More spike dry matter accumulation at peak, longer grain growth duration, better yield components such as number of grains spike-1, grain weight spike-1 and 1000-grain weight under heat stress contributed to better tolerance of BARI Gom 25, BARI Gom 26 and BARI Gom 28. The order of tolerance based on grain yield was BARI Gom 25 > BARI Gom 28 > BARI Gom 26 > Sourav and the order of tolerance based on above ground biological yield was BARI Gom 28 > BARI Gom 26 > BARI Gom 25 > Sourav. Bangladesh Agron. J. 2018, 21(1): 9-24